Perovskite Solar Cells with Carbon‐Based Electrodes – Quantification of Losses and Strategies to Overcome Them. Issue 10 (30th January 2022) - Bogachuk, Dmitry; Yang, Bowen; Suo, Jiajia; Martineau, David; Verma, Anand; Narbey, Stephanie; Anaya, Miguel; Frohna, Kyle; Doherty, Tiarnan; Müller, David; Herterich, Jan P.; Zouhair, Salma; et al.
Abstract: Carbon‐based electrodes represent a promising approach to improve stability and up‐scalability of perovskite photovoltaics. The temperature at which these contacts are processed defines the absorber grain size of the perovskite solar cell: in cells with low‐temperature carbon‐based electrodes (L‐CPSCs), layer‐by‐layer deposition is possible, allowing perovskite crystals to be large (>100 nm), while in cells with high‐temperature carbon‐based contacts (H‐CPSCs), crystals are constrained to 10–20 nm in size. To enhance the power conversion efficiency of these devices, the main loss mechanisms are identified for both systems. Measurements of charge carrier lifetime, quasi‐Fermi level splitting (QFLS) and light‐intensity‐dependent behavior, supported by numerical simulations, clearly demonstrate that H‐CPSCs strongly suffer from non‐radiative losses in the perovskite absorber, primarily due to numerous grain boundaries. In contrast, large crystals of L‐CPSCs provide a long carrier lifetime (1.8 µs) and exceptionally high QFLS of 1.21 eV for an absorber bandgap of 1.6 eV. These favorable characteristics explain the remarkable open‐circuit voltage of over 1.1 V in hole‐selective layer‐free L‐CPSCs. However, the low photon absorption and poor charge transport in these cells limit their potential. Finally, effective strategies are provided to reduce non‐radiative losses in H‐CPSCs, transport losses in L‐CPSCs, and to improve photon management in both cell types. Abstract : Despite the strong advantages of perovskite solar cells with carbon electrodes in terms of stability, their power conversion efficiencies still lag behind conventional perovskite solar cells. Here an in‐depth characterization of cells with high‐ and low‐temperature carbon‐based electrodes is presented along with the identification of their main energy losses. Promising strategies and approaches to mitigate these losses are also proposed.